Management stress in reindeer - Rehbinder, Claes (Rangifer, 1990)
The general mechanism and biological effects of stress are dealt with. Investigations performed on semidomesticated reindeer concerning the stress response under different herding and management conditions are presented and discussed. The findings indicate that: Reindeer are susceptible to management stress and that their degree of tameness plays an important role in the development of stress lesions such as muscular and myocardial degeneration and abomasal haemorrhages, etc. The animals are not favoured by rests between events of stress exposure as the effects produced tend to be cumulative. Depletion of muscular glycogen stores, increased catabolism of muscular protein, muscular degeneration and increased blood-urea levels can not be excluded as a cause of an altered and bad taste of the meat, i.e. a bad meat quality. Thus prolonged and repeated manual handling and transportation of live animals should be avoided. The use of helicopters or other motor vehicles must be correlated to the tameness of the animals and to environmental conditions. Stress due to incorrect management methods may, by means of stress induced lesions, severly affect the productivity of reindeer.